(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2024)
The algal class Bacillariophyceae (diatom) of Bangladesh is represented by nearly 291 species with almost no recent reporting of new species and/or variety. This research paper describes one new species of marine diatom Podosphenia and a variety of freshwater diatom Synedra species. The former was collected from the Bay of Bengal, Bangladesh and the latter was from Hail Haor, Srimangal, Moulvi Bazar, Bangladesh. The marine species is from genus Podosphenia Ehr. The species novo has been proposed as Podosphenia bangladeshika. A freshwater periphytic diatom from the Hail Haor wetland, Srimangal, Moulvi Bazar was initially identified as Synedra ulna due to the shape of the branched filamentous colony. The shape of the colony was quite different and looked like a twig of a green branched filamentous alga Cladophora. The species is hitherto proposed as a new variety Synedra ulna var. cladophorae. Biodivers. Conserv. Bioresour. Manag. 2024, 10(1): 75-80